The Effect of Using PhET Simulation Media on Fifth Grade Students' Learning Outcomes on Electric Materials - Rizky Annisa, Dea; Rizal, Setria Utama; Syabrina, Muhammad (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the implementation of Natural and Social Science learning using PhET simulation media and to examine its effect on students’ learning outcomes. The research adopts a quantitative approach with a pre-experimental design, employing a one-group pretest–posttest model. The participants consisted of 26 students, and data were collected through teacher and student activity observation sheets, as well as pretest and posttest assessments. The findings indicate that the use of PhET simulation media in teaching electricity was highly effective, with teacher and student activity scores averaging 97.5% and 92.3%, respectively. The mean pretest score was 51.15, which increased to 84.23 in the posttest. Because the data were not normally distributed, the Wilcoxon test was applied, yielding a significance value of 0.000 (< 0.05). These results demonstrate a statistically significant difference between pretest and posttest scores, suggesting that PhET simulation media can significantly enhance student learning outcomes in Natural and Social Science instruction.